2018
DOI: 10.21001/rap.2018.28.17
|View full text |Cite
|
Sign up to set email alerts
|

La procedencia del metal: consolidación de los estudios con isótopos de plomo en la Península Ibérica

Abstract: Se presenta el panorama seguido por la investigación en la Península Ibérica con análisis de isótopos de plomo. Destaca el impulso recibido por este tipo de análisis desde los inicios del siglo xxi y se considera que actualmente ya están consolidados como una técnica utilizada por un amplio número de investigadores y en temáticas diversas. El esfuerzo en estudiar los materiales arqueológicos ha estado acompañado también por un interés en caracterizar las zonas mineras y especialmente las minas con evidencias d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
2
0
5
Order By: Relevance
“…Therefore, we believe that it is convenient to carry out analyses such as the one presented here in order to determine the raw material used to generate the slice marks observed in pre‐Bronze sites. In the Iberian Peninsula, the evidence of metal objects is not only scarce at the beginning of the Copper Age (Díaz del Río, 2001; Montero‐Ruiz, 1994), but it is also problematic, as the presence of metal objects does not seem to be associated to a social and symbolic role as in the European context, but it is rather linked to day‐to‐day activities (Lull et al, 2010; Montero Ruiz & Murillo Barroso, 2016; Rovira, 2004). Some studies have shown that, in those cases where metal objects appear, the proportion of metal artefacts is similar both in funerary and domestic contexts (Costa Caramé et al, 2010; Montero‐Ruiz, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that it is convenient to carry out analyses such as the one presented here in order to determine the raw material used to generate the slice marks observed in pre‐Bronze sites. In the Iberian Peninsula, the evidence of metal objects is not only scarce at the beginning of the Copper Age (Díaz del Río, 2001; Montero‐Ruiz, 1994), but it is also problematic, as the presence of metal objects does not seem to be associated to a social and symbolic role as in the European context, but it is rather linked to day‐to‐day activities (Lull et al, 2010; Montero Ruiz & Murillo Barroso, 2016; Rovira, 2004). Some studies have shown that, in those cases where metal objects appear, the proportion of metal artefacts is similar both in funerary and domestic contexts (Costa Caramé et al, 2010; Montero‐Ruiz, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Aunque se trata de solo dos piezas, consideramos de interés recabar datos sobre la procedencia del metal enviándose para ello muestras al laboratorio de Geocronología de la Universidad del País Vasco (SGIker) donde se obtuvieron los resultados usando un espectrómetro de masas multicolector con fuente de plasma acoplado inductivamente (MC-ICP-MS) (table 2). Los datos han sido comparados con la información geológica y de objetos arqueológicos del Proyecto de Arqueometalurgia (Montero Ruiz, 2018 Se confirma que los dos brazaletes tienen signaturas isotópicas diferenciadas, pero debemos recordar que en el caso del brazalete nº 1 la cantidad de plomo de la aleación determina que sea la procedencia del plomo lo que identifiquemos, mientras en el nº 2 es la del cobre. El metal de PA25746 puede relacionarse o bien con las minas de Huelva dentro de la Faja Pirítica o con minas de la zona central del Valle de la Alcudia (Fig.…”
Section: Procedenciaunclassified
“…Ikerketa ugari egin da metalezko aztarna arkeologikoen jatorriaren arloan, lehengaien jatorri geologikoa ezagutzeko asmoz (Montero-Ruiz, 2018). Ikerketa horien artean, eta batez ere lan honetarako, interes handiko arloetako bat berunezko beiratuak aztertzea da, berunaren balizko jatorria argitzeko helburua duena, ondoren, balizko merkataritza-bideak iradokitzeko (Sabine, 2007;Speakman et al, 2002).…”
Section: Arloko Egoera Eta Ikerketaren Helburuakunclassified